Computational Identification of a Putative Allosteric Binding Pocket in TMPRSS2 - Sgrignani, Jacopo; Cavalli, Andrea (Frontiers in Molecular Biosciences, 2021)
Camostat, nafamostat, and bromhexine are inhibitors of the transmembrane serine protease TMPRSS2. The inhibition of TMPRSS2 has been shown to prevent viral infection of SARS coronavirus 2 (SARS-CoV-2) and other viruses. However, while camostat and nafamostat inhibit TMPRSS2 by forming a covalent adduct, the mode of action of bromhexine remains unclear. TMPRSS2 is autocatalytically activated from its inactive zymogen form through a proteolytic cleavage that promotes the binding of Ile256 to a putative allosteric pocket (A-pocket). Computer simulations, reported here, indicate that Ile256 binding induces a conformational change in the catalytic site, thus providing the atomistic rationale to the activation process of the enzyme. Furthermore, computational docking and molecular dynamics simulations indicate that bromhexine competes with the N-terminal Ile256 for the same binding site, making it a potential allosteric inhibitor. Taken together, these findings provide the atomistic basis for the development of more selective and potent TMPRSS2 inhibitors.